Odpowiedzi

2010-01-29T14:50:49+01:00
A)5x(x-3)
b)3b(y-2)
c)8x(-1y+8)
d)2a(5a-b)
e)xy(1-2)
f)6(a-4b+5c)
g)4b²(3a+4)
h)x(x²-2x+1)
i)x(2y+3-xy)
2010-01-29T14:58:05+01:00
A)=5(x²-3x)
b)=3(by-2b)
c)=8(-xy+x)
d)=2(5a²-ab)
e)=x(y-2y)
f)=6(a-4b+5c)
g)=4(3ab²+4b²)
h)=x(x²-2x+1)
2010-01-29T15:01:16+01:00
A) 5x² - 15x= 5x(x-3)
b) 3by-6b= 3b(y-2)
c) -8xy + 8x= 8x(1-y)
d) 10a²-2ab=2a(5a-b)
e) xy - x2y =xy(1-2)= xy
f) 6a-24b+30c=6(a-4b+5c)
g) 12ab²+16b²=4b²(3a-4)
h) x³-2x²+x= x(x²-2x+1)
i) 2xy+3x-x²y= x(2y +3 -xy)